"ICT INTEGRATION INTO THE MOROCCAN SECONDARY SCHOOL: AN IMPACT EVALUATION OF GENIE PROGRAMME A Dissertation Submitted in Partial Fulfillment for the Requirements of The Doctorate Degree in English Studies" - ISMAILI Jalal (Université Sidi Mohamed Ben Abdellah, Faculté des Lettres et Sciences Humaines - Saïs -, Fès, 2019)
15 years ago, the term Instructional Technology (IT) in the Moroccan public schools used to refer to mere audio-visual aids as access to high-end technology back then, namely computers, was not widely affordable. Since its inauguration in 2006, GENIE has made way for computers, video projectors, interactive whiteboards and multimedia rooms into many public schools, and has worked to add the communicative dimension to the process of technology-assisted teaching. The programme also worked on qualifying human resources to be more responsive within the new ICT enriched environment by means of occasional workshops and MOOCs. Still, in the absence of return on investment studies or impact evaluations, the programme stirred long controversy and provoked a lot of criticism by scholars, educators and auditing committees. This research project aims to study the impact of GENIE on teachers, middle and high school students and some public secondary schools using a customised six-level impact evaluation model that examines GENIE in terms of context, reaction, learning, behaviour, organisational support and outcomes. The model is based on the renowned impact evaluation models conceived by Kirkpatrick (1959), Stufflebeam (1971) and Guskey (2000). The process of data mining and analysis took advantage of both quantitative and qualitative approaches, with more emphasis on the second. The analysis of the questionnaires, interviews and related documents lead to the conclusion that the flagship ICT integration programme, in which the ministry of education invested a colossal budget that exceeds 3 Billion Moroccan Dirhams (300 million $US) between 2006 and 2015, is a promising one; however, it falls short of delivering its promise of engaging the Moroccan school into the information society as aspired to by the ministry and the government. The8 programme’s 4 axes of operation (infrastructure, training, digital resources and development of use) endure serious impediments that disturb the attainment of the programme’s objectives throughout all GENIE’s three phases of execution and will certainly hinder the realisation of the ministry’s 2030 vision. Anarchy, limited vision, weak governance and asynchrony were the most recurrent descriptions used to describe the realisation of many GENIE projects according to the surveyed participants. Because the study, which we seek to be constructive, adopts a bottom-up strategy, reactions of participants (students, teachers, headmasters and coaches) were used to help formulate remedial recommendations for decision makers and stakeholders being concerned with responding to aspirations in this regard.
Keywords: Littérature Anglaise; ICT; Instructional technology; GENIE programme; Programme evaluation; Kirkpatrick; Impact evaluation; Change management